Gays Dating Applications: Information Disclosure And Sexual Behavior - Smith , Boonchutima; Sriwattana, Sopon; Rungvimolsin, Rungroj; Palahan, Nattanop (2015)
Gay dating applications serve the drive for meeting sex partners and are now used by over 2 million gay men around the world. The nature of these apps involves users engaging in conversation that allows for significant information disclosure and increased trust, allegedly leading to unprotected sex when they meet offline. This paper therefore aims to explore the behavior of users of gay dating applications in Thailand and their pattern of information disclosure in order to investigate the relationship between app usage, information disclosure, and the resulting sexual behavior. 286 gay-dating application users in Thailand were surveyed with a self-administered, anonymous online questionnaire between February and March 2015. The findings showed significant positive association between the degree of usage and the amount of information being disclosed. Moreover, the frequency of usage such as the number of days (r = .249), the number of locations (r = .320), and the amount of time (r = .360) that the participants use the apps along with the disclosure of personal information like Facebook account (r = .337), mobile number (r = .306) and address (r = .240), are associated with the higher rate of unprotected sex. Trustworthiness deriving from information disclosure could play a vital role in the psychology of many gay men. Familiarity that develops as more information is exchanged and the level of trust increases could lead to unprotected sex. HIV/STI communication campaigns should put on emphasis on interventions conducted in gay dating applications, and publishing and promoting more content on gay-dating apps, and Facebook.